Sulfolobus – A Potential Key Organism in Future Biotechnology - Quehenberger, Julian; Shen, Lu; Albers, Sonja-Verena; Siebers, Bettina; Spadiut, Oliver (Frontiers in Microbiology, 2017)
Extremophilic organisms represent a potentially valuable resource for the development of novel bioprocesses. They can act as a source for stable enzymes and unique biomaterials. Extremophiles are capable of carrying out microbial processes and biotransformations under extremely hostile conditions. Extreme-thermoacidophilic members of the well-characterized genus Sulfolobus are outstanding in their ability to thrive at both high temperatures and low pH. This review gives an overview of the biological system Sulfolobus including its central carbon metabolism and the development of tools for its genetic manipulation. We highlight findings of commercial relevance and focus on potential industrial applications. Finally, the current state of bioreactor cultivations is summarized and we discuss the use of Sulfolobus species in biorefinery applications.